Molecular identification and evolutionary relationships between the subspecies of Musa by DNA barcodes - Dhivya, S.; Ashutosh, S.; Gowtham, I.; Baskar, V.; Harini, A. Baala; Mukunthakumar, S.; Sathishkumar, R. (BMC genomics, 2020)
The banana (Musa sp., AAA) genome is constantly increasing due to high-frequency of somaclonal variations. Due to its large diversity, a conventional numerical and morphological based taxonomic identification of banana cultivars is laborious, difficult and often leads to subject of disagreements. Hence, in the present study, we used universal DNA barcode ITS2 region to identify and to find the genetic relationship between the cultivars and varieties of banana. Herein, a total of 16 banana cultivars were PCR amplified using ITS2 primer pair. In addition, 321 sequences which were retrieved from GenBank, USA, were used in this study. The sequences were then aligned using Clustal W and genetic distances were computed using MEGA V5.1. The study showed significant divergence between the intra- and inter-specific genetic distances in ITS2 region. BLAST1 and Distance methods proved that ITS2 DNA barcode region successfully identified and distinguished the cultivar and varieties of banana. Thus, from the results of the present study, it is clear that ITS2 is not only an efficient DNA barcode to identify the banana species but also a potential candidate for enumerating the phylogenetic relationships between the subspecies and cultivars. This is the first comprehensive study to categorically distinguish the economically important banana subspecies and varieties using DNA barcodes and to understand its evolutionary relationship.